A reaction-based turn-on fluorescent sensor for the detection of Cu (II) with excellent sensitivity and selectivity: Synthesis, DFT calculations, kinetics and application in real water samples. (June 2019) - Tian, Ming; He, Huan; Wang, Bei-Bei; Wang, Xi; Liu, Yi; Jiang, Feng-Lei
Abstract: A reaction-based turn-on fluorescent chemosensor RhB-Cu, starting from rhodamine B (RhB ), for Cu 2+ was easily synthesized in two steps. The sensor could selectively detect Cu 2+ with a 100-fold fluorescence enhancement among the common metal ions, exhibiting an extremely low detection limit of 4.7 nM. To the best of our knowledge, this was the best record for the detection of Cu 2+ with organic fluorescent sensors. There was a 1:1 binding stoichiometry between RhB-Cu and Cu 2+ with an association constant of 6.42 × 10 4 M −1 . Noteworthy, it could distinguish Cu 2+ from Cu +, which was hard to realize in the previous studies. In addition, the detection mechanism was proposed based on mass spectrometric analysis and density functional theory (DFT) calculations. Kinetic studies were conducted to obtain the activation energy, enthalpy and entropy, so as to elucidate the solvent effect. Interestingly, the kinetic compensation effect (KCE) was uncovered in this work. Finally, RhB-Cu was proved to have the capability to work in real water samples. It would highly contribute to the even better design of fluorescent sensor for Cu 2+ in future. Graphical abstract: Image 1 Highlights: The probe RhB-Cu for Cu (II) had an extremely low detection limit of 4.7 nM. The probe RhB-Cu can distinguish Cu (II) from Cu (I). The kinetic compensation effect (KCE) was proved in this work.